139 nowela Justyniana I - Rominkiewicz, Jarosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article is devoted to Justinian I’s Novel 139 entitled “Remission of the penalty for unlawful marriages”. The author presents the Greek text of the novel with his own translation and commentary. Issued between 535 and 536, the novel was the ruler’s response to a petition submitted to Florus, the comes sacrarum rerum privatarum, by the inhabitants of the village of Sindys as well as Jews from Tyre. They asked in it to be allowed to stay with their wives and for their children to be regarded as legitimate, and to be spared the sanctions for incest provided for in Justinian’s Novel 12. The emperor granted such one-off pardon provided that each of them paid ten pounds of gold.
Keywords: kazirodztwo; Justynian I; nowele Justyniana; 139 nowela; prawo rzymskie; Żydzi w Tyrze; wieś Sindys; umorzenie kary za bezprawne małżeństwo